2023
DOI: 10.1177/21582440231154796
|View full text |Cite
|
Sign up to set email alerts
|

Transformational Leadership and Project Success: The Mediating Role of Psychological Empowerment

Abstract: Through the lens of social cognitive theory (SCT), we formulated hypotheses and tested the mediating role of psychological empowerment (PE) in linking transformational leadership (TL) to project success (PS). A structured questionnaire was used to gather responses from 356 team members, project managers, and stakeholders. Our findings demonstrated that PE and TL had a substantial influence on PS. Furthermore, we determined that PE partially mediates the relationship between TL and PS. This study sought to give… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 121 publications
0
5
0
Order By: Relevance
“…Agile practices are a source of empowerment (Malik et al, 2021) whichin line with the SETcan be treated as an employee benefit. Many studies have found that subordinates reciprocate this benefit by performing in accordance with leaders' preferences, in project settings as well (Fareed et al, 2023;Mubarak et al, 2021). An agile work environment stimulates general innovative behaviors in project team members (Koch et al, 2023;Malik et al, 2021), thus spurring SIBsespecially when a project leader practices SPL.…”
Section: 3mentioning
confidence: 99%
“…Agile practices are a source of empowerment (Malik et al, 2021) whichin line with the SETcan be treated as an employee benefit. Many studies have found that subordinates reciprocate this benefit by performing in accordance with leaders' preferences, in project settings as well (Fareed et al, 2023;Mubarak et al, 2021). An agile work environment stimulates general innovative behaviors in project team members (Koch et al, 2023;Malik et al, 2021), thus spurring SIBsespecially when a project leader practices SPL.…”
Section: 3mentioning
confidence: 99%
“…Along this vein, transformational leadership has been extensively investigated regarding its effects on employee task performance as developed via influences on the psychological empowerment of followers. In leadership research contexts of the individual level analysis, psychological empowerment can be treated as an independent variable affect employee motivational mechanism (i.e., Schermuly & Meyer, 2020) and employees' voice behavior (i.e., Ilyas, Abid, Ashfaq, Ali, & Ali, 2021) the final dependent variable is affected transformational leadership (i.e., Pradhan, Panda, & Jena, 2017;Schermuly et al, 2022), the mediating effects of the relationship between transformational leadership and employee work attitudes (i.e., Lan & Chong, 2015), organizational commitment (Avolio et al, 2004), innovative climate (i.e., Sagnak, Kuruoz, Polat, & Soylu, 2015), task performance and citizenship behavior (i.e., Dust, Resick, & Mawritz, 2013), career satisfaction (i.e., Joo & Lim, 2013), innovative work behavior (i.e., Grošelj, Černe, Penger, & Grah, 2021;Stanescu, Zbuchea, & Pinzaru, 2021), employee outcomes (i.e., Saira, Mansoor, & Ali, 2021), followers' attitudes (i.e., Barroso Castro, Villegas Periñan, & Casillas Bueno, 2008, organizational identification (i.e., Bose, Patnaik, & Mohanty, 2021), employees' voice behavior (i.e., Ilyas et al, 2021), project success (i.e., Fareed, Su, & Aslam, 2023), emotional labor (i.e., Cheng, Liu, & Zhou, 2023), psychological health (i.e., Tripathi & Bharadwaja, 2020), and the moderating variable between transformational leadership and organizational citizenship behavior (i.e., Jha, 2014).…”
Section: The Mediating Effect Of Psychological Empowerment On the Rel...mentioning
confidence: 99%
“…The successful management of international project activities in educational establishments involves considerations of both organizational and pedagogical conditions. We found that organizational conditions for the successful management of international project activities in educational establishments encompass the establishment of strong leadership and governance structures (Fareed et al, 2023), the formulation and adherence to a clear internationalization strategy (Melin, 1992), and the cultivation of a positive and supportive institutional culture that values diversity and innovation (Yao, 2021). Additionally, an effective organizational structure that facilitates seamless communication and coordination (Jones et al, 2020), along with the allocation of adequate financial, human, and technological resources, is essential.…”
Section: Verification Of the Organizational And Pedagogical Condition...mentioning
confidence: 99%
“…The establishment of strong leadership and governance is crucial for effectively managing international project activities in educational establishments (Fareed et al, 2023). Strong leadership provides vision, direction, and strategic oversight, while effective governance ensures that decision-making processes are transparent, accountable, and aligned with the institution's goals.…”
Section: Establishment Of Strong Leadership and Governancementioning
confidence: 99%